Logarithmic and Archimedean organic crystalline spirals - Yang, Xuesong; Lan, Linfeng; Tahir, Ibrahim; Alhaddad, Zainab; Di, Qi; Li, Liang; Tang, Baolei; Naumov, Panče; Zhang, Hongyu (Nature communications, 2024)
Crystals can be found in many shapes but do not usually grow as spirals. Here we show that applying a non-uniform layer of a polymer blend onto slender centimeter-size organic crystals prestrains the crystals into hybrid dynamic elements with spiral shapes that respond reversibly to environmental variations in temperature or humidity by curling. Exposure to humidity results in partial uncurling within several seconds, whereby a logarithmic-type spiral crystal is transformed into an Archimedean one. Conical helices obtained by lateral pulling of the spirals can wind around solid objects similar to plant tendrils or lift suspended objects with a positive correlation between the actuator’s elongation and the cargo mass. The morphological, kinematic, and kinetic attributes turn these hybrid materials into an attractive platform for flexible sensors and soft robots, while they also provide an approach to morph crystalline fibers in non-natural spiral habits inaccessible with the common crystallization approaches. The growth of crystals as spirals is unusual and this morphology can be applied to the development of flexible sensors and soft robots when the crystals respond to external stimuli. Here, the authors report the incorporation of a non-uniform layer of a polymer blend onto slender centimeter-size organic crystals to produce crystals having spiral shapes that respond reversibly to environmental variations.